Measuring patient experience with patient care coordinators during decongestion of outpatient department of an apex tertiary care referral public hospital in India - Ranjan, Rahul; Mohammad, Kausar; Singh, Angel R.; Sharma, D. K. (International Journal of Research in Medical Sciences, 2018)
Background: Specialized hospitals are faced with overcrowding in OPDs, improper behaviour of staff and navigation difficulties. In an apex tertiary care referral public hospital of India, Patient care coordinators (PCCs) were introduced to help patients navigate as a part of an OPD decongestion project. A novel concept involving patient interaction, called for measuring patient experience, to provide a baseline measurement, further improvements needed and benchmarking. For this, the model for decongestion also needed to be studied. Methods: A descriptive and cross-sectional study was conducted. Direct observations were conducted to study decongestion model and expectations from PCCs. Patient experience was measured from 400 patients using a 27-item questionnaire designed by researcher. A 5-point Likert’s scale was used for their availability, politeness, promptness, guidance, information accuracy, emotional support, etc. Dichotomous scale was also used to measure competence of PCCs. Results: A patient reception centre with three different zones was created based on status of appointments, unique hospital identification number (UHID) and new or re-visit patients. Waiting areas were created and crowd distributed based on handling capacities of sub-waiting areas dynamically adjusting to service time of doctors. PCCs facilitated navigation to right destinations. Patients had positive experience irrespective of age, gender and educational status. It related positively with a confident next visit. Conclusions: Introduction of PCCs is an effective way for assisting patient navigation. The study contributes by providing a measure of experience and benchmarking. It succinctly describes a model for decongesting OPD that may be adopted in similar settings.